Teknologi Garam Palung sebagai Warisan Sejarah Masyarakat Pesisir di Bali - Yety Rochwulaningsih, M.Si.; Mahendra Pudji Utama; Singgih Tri Sulistiyono (Jurnal Sejarah Citra Lekha, 2019)
This article aims to discuss the existence of palung salt technology as a variant of traditional solar evaporation-based salt production technology. This technology is very typical and has been used for generations by salt farmers in Bali, especially at Amed in Karangasem, Tejakula in Buleleng, and Kusamba in Klungkung. Historical and sociological method is used in this research. Palung salt technology is a historical inheritance that still functions as a cultural memory and therefore becomes a pattern for the actions of salt farmers in the three petasikan until recent time. However, since the beginning of the 21st century the preservation of palung salt technology have been faced a serious threat as a result of the inclusion of new technologies in the salt production process and especially by the growing tourism industry in palung salt production area. But, there is the awareness of stakeholders who need to preserve the technology by conducting various activities. Although carried out in a fragmentary method, efforts to preserve palung salt technology have become a shared awareness among stakeholders in the salt economy in Bali.